(untitled) (Research, Society and Development, 2022)
The subject of this article is the discussion about the unconstitutionality of item 3 provided for in the List Attached to Complementary Law nº 116/2003, so that several doctrinal positions and jurisprudential understandings that will justify this invalidity will be pointed out. The Federal Constitution regulates the Tax on Services of Any Nature, which should only apply to activities that comply with the provisions dealing with the aforementioned topic. In this approach, the basic argument is supported by the concepts of leasing and provision of services established by Private Law and in the provisions of art. 110 of the National Tax Code. The objective of the research is to demonstrate that the premises of the Binding Precedent nº 31 of the STF, which considers the incidence of ISS on the activity of leasing of movables to be unconstitutional, as well as the Presidential Veto to sub-item 3.01 of the attached list, must be extended to all item 3 of the aforementioned list, with the levy of ISS on these activities being declared unconstitutional.